God's radical grace : challenging sermons for ordinary time(s) - Ellens, J. Harold, 1932- (Newcastle-upon-Tyne, UK : Cambridge Scholars Publishing, 2013)
""As facets on a gem reveal its hidden beauty, so Dr Ellens' sermons for Ordinary Time(s) disclose the depth and beauty of the scriptures relating to these months of the Christian year between Pentecost and Advent. His long career prepared him well to author this book. With the approach of a scholar, the patience of a teacher, and the understanding of a pastor, he gives the reader new insights into these familiar scriptures. To read one of his sermons on a glorious summer day is to pray in the ...
Table of contents; foreword; praise for the book; introduction; sermon one; sermon two; sermon three; sermon four; sermon five; sermon six; sermon seven; sermon eight; sermon nine; sermon ten; sermon eleven; sermon twelve; sermon thirteen; sermon fourteen; sermon fifteen; sermon sixteen; sermon seventeen; sermon eighteen; sermon nineteen; sermon twenty; sermon twenty one; sermon twenty two; sermon twenty three; sermon twenty four; sermon twenty five; sermon twenty six; conclusion.
Print version record.
Keywords: Sermons, English; RELIGION -- Sermons -- Christian; Spirituality & religious experience; Religious life & practice; Theology; Sermons, English; Electronic books